2011
DOI: 10.1021/jf103956g
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Characterization of Dietary Fiber from Mangifera pajang Kort. Fruit Pulp

Abstract: A dried high fiber product from bambangan (Mangifera pajang Kort.) fruit pulp was prepared and evaluated for proximate composition, functional properties, and soluble and insoluble dietary fiber composition. Mangifera pajang fibrous (MPF) consisted of 4.7% moisture, 0.8% fat, 4% protein, and 30 mg total polyphenol per g of dry sample, and 9, 79 and 88% soluble, insoluble and total dietary fiber, respectively. Water holding capacity, oil holding capacity, swelling, and solubility were found to be 9 g/g dry samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 43 publications
0
39
1
Order By: Relevance
“…Adiotomre, Eastwood, Edwards, & Brydon, (1990) reported that the delay in glucose adsorption in the gastrointestinal tract could be mainly due to the fibres viscosity. The GDRI of the modified DRBDF were higher than values reported for wheat bran (Adiotomre, Eastwood, Edwards, & Brydon 1990), guar gum, apple pectin, mango peel, lemon peel and carambola pomace (Chau, Huang, & Lin, 2004) , and Mangifera pajang fiber (Sadeq et al, 2011). This may be due to the fiber structure change which can affect their hydration properties and viscosity.…”
Section: Glucose Dialysis Retardation Index (Gdri)contrasting
confidence: 42%
See 1 more Smart Citation
“…Adiotomre, Eastwood, Edwards, & Brydon, (1990) reported that the delay in glucose adsorption in the gastrointestinal tract could be mainly due to the fibres viscosity. The GDRI of the modified DRBDF were higher than values reported for wheat bran (Adiotomre, Eastwood, Edwards, & Brydon 1990), guar gum, apple pectin, mango peel, lemon peel and carambola pomace (Chau, Huang, & Lin, 2004) , and Mangifera pajang fiber (Sadeq et al, 2011). This may be due to the fiber structure change which can affect their hydration properties and viscosity.…”
Section: Glucose Dialysis Retardation Index (Gdri)contrasting
confidence: 42%
“…Untreated DRBDF, compared to modified, showed the lowest solubility (5.95±0.13 %). This solubility of micronized DRBDF was lower than that of Mangifera pajang fiber (Sadeq et al, 2011) but higher than various micronized fractions of water caltrop pericarp (Chiun, Jhih-Ying, & Po-Yuan, 2009). The solubilities of treated DRBDF were significantly different (p<0.05) from each other and it increased proportionally as the particle sizes decreased.…”
Section: Solubility and Viscosity Of Physically Modified Drbdfmentioning
confidence: 99%
“…In another study, Hassan, Ismail, Abdul Hamid, Azlan, and Al-sheraji (2011b) reported that the fibrerich powder prepared from M. pajang peel had a high amount of total dietary fibre with a balanced SDF/IDF ratio and also had a high glucose retardation index, water-holding capacity, oil-holding capacity, and swelling capacity. Moreover, in a previous study, Al-Sheraji et al (2011) investigated the soluble dietary fibre (SDF) and insoluble dietary fibre (IDF) compositions, physicochemical properties and antioxidant capacity for M. pajang fibrous (MPF) and reported that MPF contains appreciable amounts of beneficial chemical and physiochemical properties. Water-and oil-holding capacities of MPF are also important characteristics to take into account during the processing of food products that might contain this preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The flesh is about 60-65% of total weight of the fruit, bright yellow in colour, fibrous, juicy and aromatic with 5-7 mm thick skin (Al-Sheraji et al, 2011;Prasad et al, 2011). The fruit shows high antioxidant activity contributed by the phenolics, flavonoids and anthocyanin compounds (Abu Bakar, Mohamed, Rahmat, & Fry, 2009), as well as possessing cytoprotective potential against tert-butyl hydroperoxide (t-BHP) induced oxidative damage in HepG2 (Abu Bakar, Mohamed, Rahmat, Burr, & Fry, 2013).…”
Section: Introductionmentioning
confidence: 99%